PENGARUH METODE TALAQQI TERHADAP HASIL BELAJAR AL-QUR’AN HADITS SISWA KELAS VII SMPIT AL MADINAH BOYOLALI - Suha Nafisa; Laila Hidayatul Amin; Faruq Alhasbi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of the talaqqi method on seventh-grade students’ learning outcomes in Qur’an Hadith at SMPIT Al Madinah Boyolali in the 2024/2025 academic year. The research problem emerged from the varied learning outcomes of students, although the school had implemented Qur’anic learning through direct teacher guidance. This study employed a quantitative approach with a causal associative design. The population consisted of all seventh-grade students from classes VII A, VII B, and VII C. The sample included 91 students selected through total sampling. Data on the talaqqi method were collected using a closed-ended Likert-scale questionnaire, while data on learning outcomes were obtained from official documentation of daily Qur’an Hadith test scores. Data analysis included descriptive statistics, validity testing, reliability testing, normality testing, linearity testing, Pearson Product Moment correlation, and simple linear regression. The results show that the implementation of the talaqqi method was in the good category. Students’ learning outcomes had a mean score of 92.3, indicating a moderate to good category. The correlation test showed r = 0.501 with a significance value of 0.000. The regression equation Y = 71.425 + 0.615X indicates a positive effect. The R Square value of 0.251 shows that the talaqqi method contributed 25.1% to students’ learning outcomes.